2016
DOI: 10.1175/jcli-d-15-0523.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Fluxes in ERA-Interim Using Flux Tower Data

Abstract: Surface air temperature T a is largely determined by surface net radiation R n and its partitioning into latent (LE) and sensible heat fluxes (H). Existing model evaluations by comparison of absolute flux values are of limited help because the evaluation results are a blending of inconsistent spatial scales, inaccurate model forcing data, and imperfect parameterizations. This study further evaluates the relationships of LE and H with R n and environmental parameters, including T a , relative humidity (RH), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 50 publications
5
28
0
Order By: Relevance
“…1 and Table 2). Similar biases in T a within various regions worldwide have been widely reported by previous studies (Mao et al, 2010;Pitman and Perkins, 2009;Reuten et al, 2011;Wang and Zeng, 2012;Zhou et al, 2017;Zhou and Wang, 2016b). However, we found that the spatial patterns in the differences in T a are well correlated with the elevation differences between models and stations, as reflected by correlation coefficients (r) of 0.85 to 0.94 (Figs.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…1 and Table 2). Similar biases in T a within various regions worldwide have been widely reported by previous studies (Mao et al, 2010;Pitman and Perkins, 2009;Reuten et al, 2011;Wang and Zeng, 2012;Zhou et al, 2017;Zhou and Wang, 2016b). However, we found that the spatial patterns in the differences in T a are well correlated with the elevation differences between models and stations, as reflected by correlation coefficients (r) of 0.85 to 0.94 (Figs.…”
Section: Resultssupporting
confidence: 89%
“…The R s heats the surface, and the portion of this radiation that becomes the sensible heat flux heats the air near the surface (Zhou and Wang, 2016b, c;Wang and Dickinson, 2013). Part of the energy absorbed by the surface is released back to space as outgoing longwave radiation; some of this radiation is reflected by clouds and is influenced by atmospheric water vapour, further warming the near-surface air (Wang and Dickinson, 2013).…”
Section: Key Factors Regulating Regional Temperature Changementioning
confidence: 99%
See 2 more Smart Citations
“…ERA-Interim is a global atmospheric reanalysis gridded dataset available from 1979 (real time dataset from 1989 onwards) [40] at various horizontal resolutions ranging from 0.125° to 3° [41]. Meteorological variables and fluxes derived from 0.125° resolution ERA-Interim dataset roughly matches the ground observations in a study performed by Zhou and Wang [42]. ERA-Interim uses the roughness length and drag coefficient to represent the …”
Section: Methodsmentioning
confidence: 67%